2015
DOI: 10.4049/jimmunol.1500370
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-15b Modulates Japanese Encephalitis Virus–Mediated Inflammation via Targeting RNF125

Abstract: Japanese encephalitis virus (JEV) can target CNS and cause neuroinflammation that is characterized by profound neuronal damage and concomitant microgliosis/astrogliosis. Although microRNAs (miRNAs) have emerged as a major regulatory network with profound effects on inflammatory response, it is less clear how they regulate JEV-induced inflammation. In this study, we found that miR-15b is involved in modulating the JEV-induced inflammatory response. The data demonstrate that miR-15b is upregulated during JEV inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
100
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 62 publications
2
100
1
Order By: Relevance
“…Activation of RIG-I-MAVS/STING pathways during JEV infection in neurons was associated to increased production of interferon, proinflammatory cytokines and reduction of intracellular levels of virus (Nazmi et al, 2011, 2012). On the other hand, it was demonstrated that JEV infection induced the expression of microRNAs, such as miRNA15b, which negatively regulates RIG-I signaling, contributing to virus escape from innate immune response (Zhu et al, 2015). …”
Section: Flavivirus Sensing Complexesmentioning
confidence: 99%
“…Activation of RIG-I-MAVS/STING pathways during JEV infection in neurons was associated to increased production of interferon, proinflammatory cytokines and reduction of intracellular levels of virus (Nazmi et al, 2011, 2012). On the other hand, it was demonstrated that JEV infection induced the expression of microRNAs, such as miRNA15b, which negatively regulates RIG-I signaling, contributing to virus escape from innate immune response (Zhu et al, 2015). …”
Section: Flavivirus Sensing Complexesmentioning
confidence: 99%
“…In addition, roles of a number of mammalian miRNAs in response to Japanese encephalitis virus (JEV) infection have also been reported. miR-15b and miR-155 were shown to induce an inflammatory response in JEV-infected microglial cells via suppression of RNF125 (28) and SHIP1 (29), respectively, whereas miR-146a was shown to inhibit the immune response against JEV by suppressing the JAK/STAT pathway in mouse monocytes (30). WNV infection has been shown to alter the expression of the inflammatory miRNAs miR-196a, miR-202-3p, miR-449c, and miR125a-3p in the mouse brain (31).…”
mentioning
confidence: 99%
“…Several miRNAs target transcripts encoding components at many steps of the type I IFN response, which introduced an additional layer of regulation for antiviral pathway, and these targeting transcripts include components of PRR pathways impacting IFN production, the IFN cell surface receptors, signal transduction proteins to regulate IFN signaling, and some IRGs (22). In the activation of the RIG-I antiviral pathway, a set of miRNA expressions are induced and they employ feedback regulatory mechanisms to modulate type I IFN production and function (23,24). Vesicular stomatitis virus (VSV) infection induces microRNA (miR)-146a expression, which subsequently suppresses type I IFN production by targeting IL-1R-associated kinases 1 and 2 and TNFR-associated factor 6 (25).…”
mentioning
confidence: 99%